Difficulties for participation in academic activities of the National School of Public Health - Peru, 2018 - 2020 - Iguiñiz Romero, Ruth (2022)
Introduction. Dropout rates hinder the achievement of staff training goals, affecting the service they provide to the population. Objective. Identify the main difficulties and obstacles to participate in the academic activities of ENSAP, 2018-2020, that health workers report in order to improve the scope of its academic offer. Methods. Descriptive cross-sectional research at the national level applying an anonymous online Likert-type questionnaire with 44 questions, validated (Cronbach’s α of 0.888). Results. We received 3299 responses from personnel with similar general characteristics and representative of the target audience and beneficiary of ENSAP. The answers come from a mostly female sample, with nursing and / or nursing technical training, between 30 and 49 years of age. 41% have an additional job; dedicates a maximum of 5 hours / week to training and after 6:00 p.m. Excessive workload (82%), family burden (51%), poor network connection (57%), lack of recognition or compensation for training hours (49%), forgetting registration (47%) and forgetting platform´s password (41%) were the most mentioned obstacles. Conclusions. Continuous training through online modalities offers a great opportunity to reach more people at the national level. The high number of people enrolled in ENSAP activities reflects a great demand and interest in distance training, but it is necessary to propose alternatives to the obstacles they face to complete training without reinforcingexisting inequalities.